Between Baghdad and Khurasan: Early Sufism in Islamic History at 7-9 M Century - Mahendra, Fahmi Rizal; Aldiansyah, Muhammad; Wulandari, Rifdah Shofiyyah; Prakasa, Mursyidan; Faradis, Shilna (Universitas Islam Negeri Sumatera Utara, 2024)
This article describes the early movements of Sufism or Sufism in Islamic history. By using the historical method, this article explains the origins of Sufism, both from the teachings, sources, first figures and early developments in the history of early Sufism. The focus of this article is the early development of Sufism in two different areas, namely Baghdad and Khurasan. Each region gave birth to different figures, styles of thought and teachings of early Sufism. In general, the Baghdad school is famous for its